Konversi Perbankan Syariah Dari Konvensional pada Bank Umum Milik Daerah di Indonesia - Amrul Muzan; Nazla Fatimah Fatimah Hanani; Riska Riska (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The conversion of conventional banks to Islamic banks in Indonesia is one of the mechanisms for the structure of Islamic banks. That is a legal change from the conventional banking system to the Islamic banking system. The purpose of this study is to see an overview of the conversion process at the Regional Development Bank. Instant conversion can increase the amount of capital and assets of Islamic banking, but the conversion policy also raises the problem of an ineffective corporate governance mechanism model. The research method is descriptive qualitative, looking at the literature and banking reports that have been converted and are in the process of being converted to Islamic Banking. The results show that had successfully converted, some banks are in the process of converting and partially postponing. This article has implications for regional banks that want to convert to pay attention to banking problems that have been converted to Islamic Banking first.Keywords: conversion, Islamic bank, conventional bank